1
$\begingroup$

Suppose the following function with pi notation, with the pi denoting the iterated product, multiplying from $i = 0$ to $i = n$:

$$\prod_{i=0}^n \ln(y_i^{x - 1})$$

That is, the natural logarithm of $y$, subscripted by $i$, to the power of $x - 1$.

What is the derivative of this product - to be clear, its derivative with respect to $x$, not $y$?

$\endgroup$
3
  • $\begingroup$ For future reference, it is preferred you write your posts in MathJax on MSE. I have already done that for you, with some rewording and such to clarify your intent. Generally, though, it will be preferred if you include your own attempts at this problem in your post - people on MSE respond better when you include your own attempts and work, your own understanding of the problem, and the context where this pops up. As-is, I feel your post will likely accumulate downvotes and close votes despite my edits. You're more than welcome to edit your post to include these details though. $\endgroup$ – Eevee Trainer Mar 1 '19 at 2:28
  • 1
    $\begingroup$ A few further comments, now on the problem itself. What are the $y_i$'s, necessarily? Also, have you considered simply brute forcing with the product rule? There's a generalization for when you have more than $2$ functions as a product and you're trying to take the derivative of them. It's touched on in this MSE post -- math.stackexchange.com/questions/1348251/… $\endgroup$ – Eevee Trainer Mar 1 '19 at 2:30
  • $\begingroup$ Hi sorry this is my first post on MSE so I didn't know to use MathJax. Thank you for editing. I am not able to solve this as I don't understand how to proceed, and searching for the answer has proved fruitless thus I posted here. $\endgroup$ – user8115948 Mar 1 '19 at 2:35
2
$\begingroup$

We don't even need a product rule. We have \begin{align*} g(x) = \prod_{i=0}^{n}\ln(y_i^{x-1}) = (x-1)^{n+1}\prod_{i=1}^{n}\ln(y_i) \end{align*} And so \begin{align*} \frac{d}{dx} g(x) = (n+1)(x-1)^{n}\prod_{i=0}^{n}\ln(y_i) \end{align*}

$\endgroup$
1
  • $\begingroup$ Very well done! +1 $\endgroup$ – clathratus Mar 1 '19 at 5:07
1
$\begingroup$

Define $\alpha=\prod_{i=0}^n \ln(y_i)$. Note that $\alpha$ is simply a constant. Use logarithm properties, use the power rule for derivatives and you're done.

$$f(x)=\prod_{i=0}^{n}\ln{y_i}^{x-1}=\prod_{i=0}^{n}(x-1)\ln{y_i}$$$$\alpha(x-1)^{n+1}\implies \dfrac{\mathrm df}{\mathrm dx}=\alpha(n+1)(x-1)^n$$ $$\boxed{\dfrac{\mathrm d}{\mathrm dx}\prod_{k=0}^n \ln{y_i}^{x-1}=(n+1)(x-1)^n\prod_{k=0}^n\ln y_i}$$

$\endgroup$
0
$\begingroup$

Let $$f(x)=\prod_{i=0}^{n}f_i(x)$$ and let $$g^{(m)}(x)=\left(\frac{d}{dx}\right)^mg(x),\qquad m=0,1,2,...$$ as well as $\delta_{ij}$ denote the Kronecker Delta.

We have that $$f'(x)=\sum_{i=0}^{n}\prod_{j=0}^{n}f_j^{(\delta_{ij})}(x)=\sum_{i=0}^{n}\frac{f_i'(x)}{f_i(x)}f(x)$$ We use this with the choice $$f_i(x)=\ln(y_i^{x-1})=(x-1)\ln y_i$$ which gives $$f_i'(x)=\ln y_i$$ So $$f'(x)=\sum_{i=0}^{n}\frac{1}{x-1}\prod_{j=0}^{n}(x-1)\ln y_j$$ $$f'(x)=(x-1)^n\sum_{i=0}^{n}\prod_{j=0}^{n}\ln y_j$$ $$f'(x)=(x-1)^n\left(\sum_{i=0}^{n}1\right)\prod_{j=0}^{n}\ln y_j$$ $$f'(x)=(n+1)(x-1)^n\prod_{j=0}^{n}\ln y_j$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.